Impact of Virtual Reality-Assisted Role-Play on Learning Styles and English Performance - Muslim, Abd. Hakim; Setyosari, Punaji; Kuswandi, Dedi; Widiati, Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Speaking and writing skills are essential for madrasah students, as both play a crucial role in forming practical communication skills. In the context of madrasah education, where students not only study general subjects but also religious studies, having good speaking and writing skills will help them convey their ideas and understanding more clearly and precisely. This helps build self-confidence and interpersonal skills that are important in everyday life. The application of role-play is carried out not only in exact subjects but also in English language learning. The role-play environment creates a meaningful context that allows students to learn English in situations that resemble the real world. Cutting-edge technology, such as interactive, spherical video-based virtual reality (ISVVR), can be used in English language learning. Apart from being a way to overcome time constraints, ISVVR media can enrich learning resources and space for practice. This research aims to test the effect of applying role-play assisted by ISVVR and Learning Styles as moderator variables to improve English speaking and writing performance. This research used a quasi-experiment with Pre-test and Post-test Control Group Design. The participants used were 92 class XII students at MAN 5 Jombang using 2x3 factorial Manova analysis. The findings in this study were that speaking and writing performance was different between groups of students who applied role-play assisted ISSVR and conventional video and learning styles, but there was no interaction between model and learning style on speaking and writing performance.